Changes in prevalence of loneliness among home-dwelling older adults over three decades and associated factors - Mia T. Knuutila; Laura J. Rautiainen; Ulla L. Aalto; Tuuli E. Lehti; Helena Karppinen; Hannu Kautiainen; Timo E. Strandberg; Hanna Reeta Öhman; Niina M. Savikko; Anu H. Jansson; Kaisu H. Pitkälä (Experimental Gerontology)
Background: Studies examining loneliness trends over several decades among comparable cohorts of older people are rare. Objective: We evaluated how the prevalence of self-reported loneliness has changed over three decades among home-dwelling older people (75+ years), and factors associated with loneliness. Methods: We used data from four waves of the Helsinki Aging Study (1989-present), a repeated cross-sectional cohort study. The data had been collected using a postal questionnaire. The sample sizes were: 1989 (n = 660), 1999 (n = 2598), 2009 (n = 1637), 2019 (n = 1758). Based on responses to the question “Do you suffer from loneliness?”, we categorized the respondents into lonely (‘always or often’, ‘sometimes’) and not lonely (‘seldom or never’). The associations between various characteristics and loneliness were explored. Results: The prevalence of loneliness among older people decreased slightly between 1989 and 2019, from 34 % to 30 %. Loneliness decreased among both sexes. In the multivariable forward stepwise regression model, factors associated with loneliness were widowhood (OR 2.18, 95 % CI 1.91–2.49), needing help daily (OR 1.83, 95 % CI 1.56–2.16), feeling depressed (OR 5.26, 95 % CI 3.56–7.77), comorbidities (OR 1.07, 95 % CI 1.03–1.11), feeling useful (OR 0.36, 95 % CI 0.31–0.41), meeting friends (OR 0.65, 95 % CI 0.57–0.74), and male sex (OR 0.69, 95 % CI 0.59–0.80). Conclusions: Loneliness among both older men and women has decreased over the past three decades. Several factors were found to be associated with loneliness. Given the detrimental impact of loneliness on health of individuals, policies and health strategies aimed at alleviating loneliness among older people should be a top priority.